2016
DOI: 10.1016/j.neuroscience.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the oxytocin system in amygdala subregions in the regulation of social interest in male and female rats

Abstract: We previously found that oxytocin (OT) receptor (OTR) binding density in the medial amygdala (MeA) correlated positively with social interest (i.e., the motivation to investigate a conspecific) in male rats, while OTR binding density in the central amygdala (CeA) correlated negatively with social interest in female rats. Here, we determined the causal involvement of OTR in the MeA and CeA in the sex-specific regulation of social interest in adult rats by injecting an OTR antagonist (5 ng/0.5 µl/side) or OT (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…One possible explanation for these findings is that overstimulation of the brain OXT system with WAY-267464 in control males may result in reduced drive/need for social interaction. Indeed, under normal circumstances exposure to a conspecific in male rodents stimulates OXT release in the brain (Dumais et al 2016), and the combination of these two sources of OXT-R stimulation may be sufficient to elevate OXT-R activation beyond optimal levels and induce suppression of social behavior, a suggestion consistent with frequent indications of inverted U-shaped functions relating activation of various peptide systems and behavior (e.g., Boccia et al 1998). …”
Section: Discussionmentioning
confidence: 83%
“…One possible explanation for these findings is that overstimulation of the brain OXT system with WAY-267464 in control males may result in reduced drive/need for social interaction. Indeed, under normal circumstances exposure to a conspecific in male rodents stimulates OXT release in the brain (Dumais et al 2016), and the combination of these two sources of OXT-R stimulation may be sufficient to elevate OXT-R activation beyond optimal levels and induce suppression of social behavior, a suggestion consistent with frequent indications of inverted U-shaped functions relating activation of various peptide systems and behavior (e.g., Boccia et al 1998). …”
Section: Discussionmentioning
confidence: 83%
“…We recently showed that adult male and female rats have similar levels of endogenous OT release (Dumais et al, 2016a) and similar OTR binding density (Dumais et al, 2013; Smith et al, 2016) in the central amygdala. However, we now show that the response to exogenous OT elicits sex-specific activation of the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we examined blood oxygen level dependent (BOLD) activation in awake male and female rats following central (ICV) or peripheral (intraperitoneal; IP) OT administration. The sex-specific effects of OT on social behavior (Dumais et al, 2016a, 2016b) as well as the sex differences in OTR binding density (Dumais et al, 2013) in rats led us to hypothesize that ICV OT administration would elicit sex differences in neural activation Because peripheral OT has hampered access to the brain (Mens et al, 1983; Ermisch et al, 1985), and knowledge of sex differences in peripheral OTR is limited (except for on reproductive systems; Gimpl and Fahrenholz, 2001), we hypothesized that there would be fewer sex differences in neural activation following IP OT administration compared to ICV administration.…”
Section: Introductionmentioning
confidence: 99%
“…Although all magnocellular neurones project to the posterior pituitary, subpopulations project to various central sites including the nucleus accumbens, hippocampus, amygdala and bed nucleus of the stria terminalis. [179][180][181][182][183][184] Vasopressin and oxytocin are released not only from nerve terminals in response to spike activity, but also from the soma and dendrites in response to the mobilisation of intracellular Ca 2+ . It is likely that, within the brain, oxytocin cells release not only glutamate at synapses in the manner typical of neurotransmitters, but also occasional vesicles containing oxytocin from axonal varicosities to act as a local neuromodulator.…”
Section: Con Clus Ionsmentioning
confidence: 99%